THE CHANGE OF MANAGEMENT ON TANJUNG PUTUS LAKE KUALA TERUSAN VILLAGE OF PANGKALAN KERINCI SUB DISTRICT THE PALELAWAN DISTRICT OF THE RIAU PROVINCE - Prasetya, Budi; Hendrik, Hendrik; Hamid, Hamdi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            This research was coducted in September 2016 in the Kuala Terusan Village Pangkalan Kerinci sub district of  Pelalawan districtof the Riau provincial The purpose of this study is to : know the description of the changes in the management of lake dropes offshore Kuala Terusan village the Pangkalan Kerinci regency Pelalawan district of Riau Province. The methode used in this research is case study methode with qualitative approach. The determination of informan using snowball sampling technique and data collection in the form of primary and secondary data.            The result of the research shows the picture change of the management Tanjung Putus lake of Kuala Terusan villagethe Pangkalan Kerinci sub district the Pelalawan district of the Riau Province, the cause of the change in the management of the drooping lagoon consist of several factors, namely the increasing of population, the lack of supervision from the community and Ninik Mamak, the technological of development and the economic need.While the efforts that heve been done in maintaining the management of fishery resources of Tanjung Putus lake consist of regulation and sanctions, as well as conducting lake autions once a year.Keyword : Management, Fishery Resources, Conservation, sanctions